INTEGRATION OF TEACHING THE LANGUAGE SKILLS WITH INFORMATIONAL TECHNOLOGIES (SCIENCE TIME JOURNAL, 2025)
The integration of Information Technologies (IT) into language education has been transformative, enabling the enhancement of language skills through interactive, engaging, and personalized learning experiences. This paper explores the various methods by which IT can be integrated into language teaching to improve listening, speaking, reading, writing, grammar, vocabulary, and cultural awareness. The study examines how digital tools, such as language learning apps, speech recognition, e-learning platforms, and gamification, contribute to language proficiency. It also discusses the benefits and challenges of integrating these technologies into educational settings. The findings suggest that while IT facilitates learner engagement and access to authentic materials, there are challenges in terms of technological access, teacher preparedness, and balancing technology with traditional teaching methods.